The Effects of Information and Emotional Support Program on Uncertainty of Illness and Stress Coping among Caregivers of Traumatic Brain Injury Patients - Arammuang, Sakulwan; Toskulkao, Tipa; Leelahakul, Venus (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
This study was a quasi-experimental research with a two group pretest-posttest design. The purpose of the study was to examine the effect of the Information and Emotional Support Program on uncertainty of illness and stress coping among caregivers of traumatic brain injury patients. The samples comprised 58 traumatic brain injury patients’ caregivers in neurosurgical ward, Ratchaburi hospital. The samples was conveniently selected according to the specific criteria. They were assigned into the experimental or the control groups, Each group consisted of 29 participants. The experimental group received the Information and Emotional Support Program for 5 days and the control group received the usual nursing care. Data were collected using the demographic of patients and caregivers data form and uncertainty of illness and stress coping questionnaires. The reliability of uncertainty of illness and stress coping questionnaire using Cronbach’s alpha coefficient were .76 and .71, respectively. The data were analyzed by using descriptive statistics and ANCOVA. The results revealed that after receiving the program, the experimental group had significantly lower uncertainty of illness than the control group [F(1,55) = 44.697, p< .001]. The experimental group had significantly better stress coping than the control group [F(1,55) = 23.590, p < .001]. Hence, nurses may add this program to the usual nursing care in order to promote better quality of care provided by caregivers of traumatic brain injury patients.